Case Report : Nursing Asessment of Patients CKD with Post History Operation Tumormamae - Dewi Ratnasari; Nur Isnaini (UM Purwokerto Press, 2021)
Chronic Kidney Disease is a deterioration of kidney function that occurs for 3 months or more. A person with CKD usually does not show any symptoms, but a person can experience several signs throughout his body such as loss of appetite, fatigue, water-electrolyte imbalance and so on. Therefore, an assessment is needed to clarify the medical diagnosis of whether a person suffers from CKD or not.To describe the stages of assessment in patients with an early diagnosis of CKD.The study was conducted in the Darussalam room, collecting data using auto-anamnesis, direct assessment, and physical examination.The results of the assessment phase obtained abnormal data on the respiratory, digestive, cardiovascular, urinary, musculoskeletal and integumentary systems. In Mrs.S the whole system almost experiences the symptoms mentioned in theory when a person has CKD.In accordance with the theory of Mrs. S shows most of the signs and symptoms that appear in CKD patients. This was also reinforced by supporting examinations which confirmed that Mrs. S was diagnosed with CKD and was required to undergo hemodialysis at the hospital.